نظرية الأصل والفرع وتطبيقاتها في النصوص النحوية: كتاب الأمالى النحوية لابن الحاجب ت. 646 هـ. أنموذجا - بودرامة، الزايدى (جامعة الأمير عبد القادر للعلوم الإسلامية, 2016)
تعد فكرة الأصل والفرع إحدى الدعائم التي أقيم عليها الدرس اللغوي العربي في جميع المستويات التي عالجها) الصوتية، والصرفية، والتركيبية، والدلالية، والبلاغية (ويجد المطلع على مضامينها أن لها دورا تنظيميا-بل تتجاوزه إلى أغراض أخرى -وقد تمكن الدارسون، بفضل اعتمادها، من تقديم قضايا في المعالجة والنظر والتحليل على أساس أنها الأصل، وتأخير أخرى وإلحاقها بالأولى لأنها فرع. وسيحاول المقال تتبع هذه الفكرة) الأصل والفرع (في المدونة النحوية العربية، مختارا كتاب الأمالي لابن الحاجب عينة للدراسة، من أجل التدليل أكثر على قيمتها ودورها في النظرية النحوية العربية.
The idea of the root and the branch is one of the fundamental pillars of the Arab language lesson, in all levels that has already treated: phonetic, morphological, syntactic, semantic and rhetorical level. Who will review its concepts can be found that it has an organizing role among other roles .After the Arab researchers adopted it, they advanced some theses concerning the processing and the analysis, because they belong to the root, and roll back other theses and annexed to the first because they belong to the branch. This article will try to pursue this idea of "the root and the branch” in the Arabic grammatical corpus by taking as a study sample the book of Ibn El Hadjeb entitle[Al Amali] (that means hopes) to demonstrate the importance and the role of this idea in the Arabic grammatical theory.
Keywords: اللغة العربية -- النصوص النحوية -- كتاب الأمالى النحوية -- ابن الحاجب، عثمان بن عمر بن أبي بكر، 646 هـ. -- تحقيق المخطوطات